PANDANGAN INDONESIA TERHADAP HAK ASASI MANUSIA DI BIDANG POLITIK DITINJAU DARI UUD 1945 SETELAH AMANDEMEN - Ramon Kaban (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
As a modern democracy state that was born after the World War II, Indonesia should guarantee the enforcement of human right on politics for the society. Therefore constitutional development of Indonesia are demanded to be able to follow the era development. It can be done by doing amendment on Paragraph 28 of Constitution 1945 of Year 2000 as a second amendment. The amendment reflects Indonesia point of view that are more modern and open in organizing the human right on the constitution as an explanation of advance point of view on human right for sure.